Analitik Big Data: Social Media Mining - Annisa Rahmala; Don Ardhito; Leo Riska (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2022)
he development of big data from year to year has become very rapid in line with the development of the Internet of Things (IoT). One of the most widely owned and frequently used devices is a mobile phone, especially a smartphone. Social media applications found on smartphones generate large amounts of data every second. These data are widely used forresearch in various fields of big data analytics. And the techniques used also vary depending on the dataset and the purpose of the research. This study aims to discuss big data analytics, especially social media mining, and some of its techniques for analysis. The research was conducted using a literature review method on journals and books discussing topics relevant to this research. The expected benefit of this research is that it can add insight and knowledge for readers who are interested in the topic of social media mining.